Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2023
DOI: 10.18608/jla.2023.7801
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Explanations in Automated Essay Scoring Systems on Student Trust and Motivation

Abstract: Ethical considerations, including transparency, play an important role when using artificial intelligence (AI) in education. Explainable AI has been coined as a solution to provide more insight into the inner workings of AI algorithms. However, carefully designed user studies on how to design explanations for AI in education are still limited. The current study aimed to identify the effect of explanations of an automated essay scoring system on students’ trust and motivation. The explanations were designed usi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 70 publications
0
5
1
Order By: Relevance
“…The trust evaluation method utilized in our study allowed us to evaluate the initial user trust in a more detailed view. As no control group was included in our study, our findings are not directly comparable to [28], who reported no difference in trust between students who observed any of the two explanations and those in the control group. The results of this study have contradicted the existing literature on LA systems about the recognized effect that explanations have on user trust.…”
Section: Discussioncontrasting
confidence: 95%
See 2 more Smart Citations
“…The trust evaluation method utilized in our study allowed us to evaluate the initial user trust in a more detailed view. As no control group was included in our study, our findings are not directly comparable to [28], who reported no difference in trust between students who observed any of the two explanations and those in the control group. The results of this study have contradicted the existing literature on LA systems about the recognized effect that explanations have on user trust.…”
Section: Discussioncontrasting
confidence: 95%
“…The need for the interpretability of the complex models used in education mining data techniques has been highlighted [26], and explanations of the model's predictions have been introduced slowly, by [27] offering verbal explanations (i.e., "Evaluation is Pass because the number of assessments is high"), and by [10] offering verbal and visual explanations to students. In a related study, Conijn et al [28] analyzed the effects of explanations of an automated essay scoring system on students' trust and motivation in the context of higher education. The results indicated there is no one-size-fits-all explanation for different stakeholders and in different contexts.…”
Section: Xai In Educationmentioning
confidence: 99%
See 1 more Smart Citation
“…Overreliance on AI may reduce students' intrinsic motivation to write autonomously, limiting their creative and independent writing. Conijn et al, 2023;Gayed et al, 2022;Ouyang et al, 2022 Limited transferable skills AI-generated work may lack the critical thinking and analysis that companies and graduate programs value.…”
Section: Overdependence On Technologymentioning
confidence: 99%
“…The significance of this study lies in the need to critically examine the role of AI in an essential component of university curricula -developing students' abilities in academic writing and composition. Strong writing skills are foundational for communicating ideas effectively, conducting research, critically analyzing texts, and succeeding in many educational and professional domains (Conijn et al, 2023;Zhai & Ma, 2022). However, the rise of AI writing assistants raises concerns about an overreliance on technologies that may impede the fostering of these crucial skills.…”
Section: Introductionmentioning
confidence: 99%